2021
DOI: 10.1002/bse.2857
|View full text |Cite
|
Sign up to set email alerts
|

Connecting strategic orientation, innovation strategy, and corporate sustainability: A model for sustainable development through stakeholder engagement

Abstract: This paper aims to enhance our understanding of the relationship between organizations ' strategic orientation (i.e., instrumental, equidistant, and stewardship) and their innovational strategy (i.e., organizational ambidexterity and open innovation), and this relationship's influence on their sustainability performance. We expected organizations' strategic orientation to influence their innovational strategy and exhibit better corporate sustainability. We focused on 12 different multinational organizations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
7

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 74 publications
0
38
0
7
Order By: Relevance
“…Green practices have been planned and implemented as an effective business strategy to help firms fulfill environmental objectives and create unique value for customers and society (Khanra et al, 2022; Kumar et al, 2021; van Lieshout et al, 2021). In the hospitality industry, green practices are an essential part of a green strategy that hospitality companies engage in for sustainable development (Assaker, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Green practices have been planned and implemented as an effective business strategy to help firms fulfill environmental objectives and create unique value for customers and society (Khanra et al, 2022; Kumar et al, 2021; van Lieshout et al, 2021). In the hospitality industry, green practices are an essential part of a green strategy that hospitality companies engage in for sustainable development (Assaker, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Companies use first‐order DCs, namely, essential resources, to increase competitive advantages and cope with changing environments (Zhang, 2014). The current volatile market conditions in which corporations operate make it hard for a corporation to achieve sustainable competitive advantages (van Lieshout et al, 2021). In fact, currently, companies are experiencing a new context where stakeholders scrutinize their sustainable practices.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, companies that have been exposed to exploratory principles of search, variation and risk‐taking respond to stakeholder pressures by venturing into sustainable practices, with a long‐term focus on profit‐making, a typical characteristic of exploratory activities (van Lieshout et al, 2021). Solís‐Molina et al (2018) have recognized that a company performs better with ambidexterity in some cases.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…The research questions of the extracted contributions (that are reported in Table 2) indicated that in many cases, companies are striving in their endeavors to build productive relationships with different stakeholders (Mtapuri et al, 2022;Peña-Miranda et al, 2022;Shaikh & Randhawa, 2022), to create value to their businesses as well as to society (Döll et al, 2022;Ghodbane, 2019;Roszkowska-Menkes, 2018). Very often, they confirmed that open innovation practitioners are promoting organizational governance (Aakhus & Bzdak, 2015;Sánchez-Teba et al, 2021), fair labor practices (Chang, 2020;Herrera & de las Heras-Rosas, 2020;Kumar & Srivastava, 2020;Schmidt-Keilich & Schrader, 2019), environmentally responsible investments (Aakhus & Bzdak, 2015;Cigir, 2018;Mendes et al, 2021;van Lieshout et al, 2021;Yang & Roh, 2019), and consumer-related issues (Greco et al, 2022;Loučanová et al, 2022;Wu & Zhu, 2021;Yang & Roh, 2019), among other laudable behaviors.…”
Section: Open Innovation Opportunitiesmentioning
confidence: 97%
“…Currently, there are limited perspectives in academia linking open innovation approaches with the business ethics literature (Amor‐Esteban et al, 2019; Roszkowska‐Menkes, 2018). Even fewer are elaborating on the importance of forging fruitful and collaborative agreements with internal and external stakeholders, to foster social innovations in terms of environmental, social, and governance (ESG) performance (Ben Hassen & Talbi, 2022; Camilleri, 2022b; Ghodbane, 2019; Herrera & de las Heras‐Rosas, 2020; Kumar & Srivasava, 2020; Roszkowska‐Menkes, 2018; van Lieshout et al, 2021). Therefore, this contribution addresses a knowledge gap in academia.…”
Section: Introductionmentioning
confidence: 99%